Brillouin backscattering analysis in recent generation of telecom optical fibers - Lakomski, Mateusz; Tosik, Grzegorz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
This paper reports on examination of the latest generation of telecom optical fibers for the Brillouin backscattering strain sensor application. Over 30 fibers from 5 different manufactures have been tested in terms of their ability to create a stable and accurate strain sensor. It has been proved that fibers that belong to the same standard, according to ITU-T (International Telecommunication Union), and even if provided by one manufacturer, demonstrate fundamentally different Brillouin backscattering response. It has been shown that unimodal Brillouin spectrum cannot be treated as the main parameter for fiber selection. In order to achieve accurate and reproducible results of strain measurement, it is necessary to perform initial examination of the fibers over the range of laser pulse width.
Optica Applicata, Vol. 52, 2022, nr 3, s. 405-416
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; Brillouin backscattering; optical fiber; optical fiber application; optical fiber sensors; strain measurement